2014
DOI: 10.1097/jcn.0b013e318291ee43
|View full text |Cite
|
Sign up to set email alerts
|

Morning Blood Pressure Surge and Nighttime Blood Pressure in Relation to Nocturnal Sleep Pattern and Arterial Stiffness

Abstract: Our findings imply a possible link between disturbed sleep and MBPS. Clinicians should understand the importance of the modification of altered sleep pattern for reducing MBPS in nonhypertensive participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
0
13
0
2
Order By: Relevance
“…Suh et al . () studied 30 healthy Korean American women aged 25–60 years and concluded that there was a possible link between disturbed sleep and morning surge. Our study showed that behaviour and chronotherapy intervention could improve BP surge in the morning, which could decrease the cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Suh et al . () studied 30 healthy Korean American women aged 25–60 years and concluded that there was a possible link between disturbed sleep and morning surge. Our study showed that behaviour and chronotherapy intervention could improve BP surge in the morning, which could decrease the cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…5 This finding could result from the link between greater arterial stiffness, as measured by carotid-femoral pulse wave velocity, and higher morning SBP. 10 Basal sympathetic tone and the risk of hypertension (HTN) and related cardiovascular disease both vary with ethnicity. 11 African Americans have a disproportionately high prevalence and severity of HTN compared with other racial groups in the USA.…”
mentioning
confidence: 99%
“…30 There is a paucity of studies investigating the relationship between arterial stiffness and MBPS. Suh et al 2 studied the association of MBPS with PWV in healthy Korean women. They showed that although arterial stiffness did not show significant association with MBPS, it was associated with higher morning BP.…”
Section: Discussionmentioning
confidence: 99%
“…28 Because pulse wave travels faster in arteries with decreased elasticity, arterial stiffness could be measured by PWV. 2 Augmentation index (AIx) is a composite index that integrates the amount of wave that is reflected back to aorta and the velocity of incident and reflected wave. 29 Aortic PWV and AIx are indices of arterial stiffness and are predictors for cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation